2020
DOI: 10.2147/ijgm.s278564
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA A2M-AS1 Promotes Breast Cancer Progression by Sponging microRNA-146b to Upregulate MUC19</p>

Abstract: Background: Long non-coding RNA (lncRNA) A2M-AS1 has been indicated to be augmented in breast cancer (BC), with its specific function undetermined. Therefore, this study is designed to investigate the mechanism of lncRNA A2M-AS1 in BC. Methods: The expression of A2M-AS1, microRNA (miR)-146b, and MUC19 in BC tissues and cells was measured. Then, the interaction among A2M-AS1, miR-146b, and MUC19 was detected. After A2M-AS1, miR-146b, and MUC19 expression were altered in BC cells, cell proliferation, invasion, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…MUC19 reportedly modulates proliferation, invasion and metastatic potential of breast cancer [ 80 ]. MUC19 expression was notably observed to increase in TNBC and found to be targeted by miR-593 [ 81 ]. KCNB1 is a complex class of voltage-gated ion channels and its overexpression was reported as biomarker in breast cancer [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…MUC19 reportedly modulates proliferation, invasion and metastatic potential of breast cancer [ 80 ]. MUC19 expression was notably observed to increase in TNBC and found to be targeted by miR-593 [ 81 ]. KCNB1 is a complex class of voltage-gated ion channels and its overexpression was reported as biomarker in breast cancer [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that MUC19 was significantly upregulated in BC ( 38 ) and that patients with high MUC19 expression levels exhibited a worse prognosis ( 39 ). Liu et al ( 40 ) reported that MUC19 promotes cell proliferation, invasion and colony formation and inhibits apoptosis in BC. The present study also demonstrated that MUC19 was significantly upregulated in BC and promoted BC cell proliferation and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Three lncRNAs ( A2M-AS1 , C2orf27A , and ZNF667-AS1 ) were identified to be related to the hub FRGs. Among them, A2M-AS1 was reported to be involved in the invasion, migration, and progression of breast cancer ( Fang et al, 2020 ; Liu et al, 2020b ). In addition, A2M-AS1 was also reported to lessen cardiomyocyte injury caused by hypoxia/reoxygenation (H/R) by regulating IL1R2 ( Song et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%